2019
DOI: 10.1021/acs.jpcc.8b12575
|View full text |Cite
|
Sign up to set email alerts
|

Directing Long-Range Molecular Ordering in Ionic Liquid Films: A Tale of Two Interfaces

Abstract: We report surface-dependent, long-range ordering behavior of two ionic liquids, 1-butyl-1-methylpyrrolidinium tetracyanoborate (P14 B­(CN)4) and 1-butyl-1-methylpyrrolidinium dicyanamide (P14 N­(CN)2). The ionic liquids are supported as liquid films and examined using vibrational spectroscopy and spectroscopic ellipsometry. Both systems show changes in the infrared peak profile characteristic of major dipole reorientations for both anions, but the changes observed are in different spectral regions. Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 44 publications
(85 reference statements)
0
30
0
Order By: Relevance
“…In these efforts, in addition to the well-established electrochemical metrology, advanced optical, microscopy, and scattering techniques have been utilized. These have revealed that the screening dynamics evolving on multiple time and length scales are due to various diffusion and relaxation processes. This has been also corroborated by simulations. , These studies have revealed that the polarization of ILs includes medium–slow (0.1 s–10 s) and ultraslow (10 2 –10 4 s) evolutions, in addition to the fast electrical double-layer (EDL) formation (1–10 ns), which also proceeds on short (1–10 nm), medium (<1 μm), and long (>100 μm) length scales. Therefore, for extended IL devices, the information reflecting not only the solid/liquid interface but also the bulk liquid and electrodes must be accounted for comprehensive analyses.…”
Section: Introductionmentioning
confidence: 68%
“…In these efforts, in addition to the well-established electrochemical metrology, advanced optical, microscopy, and scattering techniques have been utilized. These have revealed that the screening dynamics evolving on multiple time and length scales are due to various diffusion and relaxation processes. This has been also corroborated by simulations. , These studies have revealed that the polarization of ILs includes medium–slow (0.1 s–10 s) and ultraslow (10 2 –10 4 s) evolutions, in addition to the fast electrical double-layer (EDL) formation (1–10 ns), which also proceeds on short (1–10 nm), medium (<1 μm), and long (>100 μm) length scales. Therefore, for extended IL devices, the information reflecting not only the solid/liquid interface but also the bulk liquid and electrodes must be accounted for comprehensive analyses.…”
Section: Introductionmentioning
confidence: 68%
“…7,11–13 The Fayer group, in a series of elegant experiments using small molecules as probes, has identified organization with a persistence length on the order of tens to hundreds of nm in RTILs, 14–19 and the Shaw group has identified the evolution of structural order on the micrometer length scale in thin RTIL films. 20–23 Very recently, the Welton group has identified spatial variation in n , the refractive index, over distances of tens to hundreds of nm using Raman scattering. 24 It is clear from all these studies that RTILs exhibit structural order over length scales vastly in excess of what is typical for liquid phase solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we attempt to understand the characteristic electric field effects on the Raman spectra of the ILs in the context of the Pockels effect because the Δ I signal has been found to be proportional to the applied potential E (see Figure S2b). The Pockels effect occurs only in non-centrosymmetric media like crystals, but if some ordering is induced in ILs near the interface with an electrode as revealed in recent studies, it could break the inversion symmetry and allow the Pockels effect to occur in the interfacial region of the IL. The resulting change in the refractive index, Δ n (= a 1 F ), would then affect the power of the excitation light at the focal point ( I exc in eq ) through eqs and .…”
Section: Resultsmentioning
confidence: 98%
“…18,19 scale ordering can be induced in IL fluid films has been gained by IR reflection absorption spectroscopy and second harmonic generation. 20,21 Even greater organization on the order of 100 μm has been suggested by other laboratories for ILs at a charged surface. 22−24 The electric field effects on ILs are a crucial key to address the controversial question of the length scale of such an organization.…”
Section: ■ Introductionmentioning
confidence: 86%
See 1 more Smart Citation